Flow And Sediment Pattern Simulation At Ijok Intake, District Of Larut Matang, Perak - Shahidan, Noor Fareezianna Noor (2012)
Rapid development near the river systems can contribute to morphology changes due to increased or decreased sediment carrying capacity, erosion and deposition along the channel. Understanding the sedimentation processes in the river engineering, and hydraulic structures are of vital importance as this can affect water supply for the agricultural lands in the command area. To understand the problem, frameworks of physical and mathematical modeling were applied to investigate the flow and sediment pattern at Ijok Intake, Ijok River, Malaysia. HEC-RAS (1D modeling) and CCHE2D (2D modeling) software were used as the mathematical model where results from HEC-RAS were used as input for CCHE2D.